2008
DOI: 10.1103/physrevd.78.064073
|View full text |Cite
|
Sign up to set email alerts
|

Higher dimensional slowly rotating dilaton black holes in AdS spacetime

Abstract: In this paper, with an appropriate combination of three Liouville-type dilaton potentials, we obtain the higher dimensional charged slowly rotating dilaton black hole solution for asymptotically anti-de Sitter spacetime. The angular momentum and the gyromagnetic ratio of such a black hole are determined for the arbitrary values of the dilaton coupling constant. It is shown that the dilaton field modifies the gyromagnetic ratio of the rotating dilaton black holes.Comment: 11 pages, 1 figure, the version to appe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…This is due to the fact that the dilaton field does not vanish for r → ∞. Latter, it was shown that with combination of three Liouville type dilaton potentials, it is possible to construct dilatonic black hole solutions in the background of (A)dS spacetime [16][17][18][19][20]. Recently, studies on compact objects such as neutron stars in the context of dilaton gravity [21,22] as well as black objects in dilaton gravity's rainbow have been carried out [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that the dilaton field does not vanish for r → ∞. Latter, it was shown that with combination of three Liouville type dilaton potentials, it is possible to construct dilatonic black hole solutions in the background of (A)dS spacetime [16][17][18][19][20]. Recently, studies on compact objects such as neutron stars in the context of dilaton gravity [21,22] as well as black objects in dilaton gravity's rainbow have been carried out [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…While asymptotically (anti-)de Sitter vacuum black holes are known [35], their generalizations to Einstein-Maxwell theory are known only either numerically [36][37][38] or in the limit of slow rotation [39,40]. Slowly rotating (anti-) de Sitter black holes were also considered with a dilaton field included [41,42].…”
Section: Discussionmentioning
confidence: 98%
“…This forces us to restrict ourselves to the limit of slow rotation. Slowly charged rotating black hole solutions in higher dimensions with a single rotation parameter have been investigated by many authors [38][39][40][41][42][43][44][45][46]. Using perturbation theory, they have introduced the rotation parameter as a perturbative parameter and solved the equations of motion up to the linear order of the angular momentum parameter.…”
Section: Introductionmentioning
confidence: 99%